The First Use of Coordinated Ionospheric Radio and Optical Observations Over Italy: Convergence of High‐and Low‐Latitude Storm‐Induced Effects. Issue 11 (26th November 2017) - Cesaroni, C.; Alfonsi, L.; Pezzopane, M.; Martinis, C.; Baumgardner, J.; Wroten, J.; Mendillo, M.; Musicò, E.; Lazzarin, M.; Umbriaco, G.
Abstract: Ionospheric storm effects at midlatitudes were analyzed using different ground‐based instruments distributed in Italy during the 13–15 November 2012 geomagnetic storm. These included an all‐sky imager (ASI) in Asiago (45.8°N, 11.5°E), a network of dual‐frequeny Global Navigation Satellite Systems receivers (Rete Integrata Nazionale GPS network), and ionosondes in Rome (41.8°N, 12.5°E) and San Vito (40.6°N, 17.8°E). GPS measurements showed an unusual enhancement of total electron content (TEC) in southern Italy, during the nights of 14 and 15 November. The ASI observed colocated enhancements of 630 nm airglow at the same time, as did variations in N m F 2 measured by the ionosondes. Moreover, wave‐like perturbations were identified propagating from the north. The Ensemble Empirical Mode Decomposition, applied to TEC values revealed the presence of traveling ionospheric disturbances (TIDs) propagating southward between 01:30 UT and 03:00 UT on 15 November. These TIDs were characterized by weak TEC oscillations (~ ±0.5 TEC unit), period of 45 min, and velocity of 500 m/s typical of large‐scale TIDs. Optical images showed enhanced airglow entering the field of view of the ASI from the N‐NE at 02:00 UT and propagating to the S‐SW, reaching the region covered by the GPS stations after 03:00 UT, when TEC fluctuations are very small (~ ±0.2 TEC unit). The enhancement of TEC and airglow observed in southern Italy could be a consequence of a poleward expansion of the northern crest of the equatorial ionization anomaly. The enhanced airglow propagating from the north and the TEC waves resulted from energy injected at auroral latitudes as confirmed by magnetometer observations in Scandinavia. Key Points: Persistent enhancements to the southeast in F layer ionization and airglow due to an unusual poleward excursion of the low‐latitude ionosphere High‐latitude brightness wave in 630.0 nm airglow observed traveling N‐NE to S‐SW that encountered the stationary enhancement in the SW Empirical Mode Decomposition results on total electron content found wave activity with LSTID characteristics, preceding the optical wave